1992
DOI: 10.1097/00004032-199206000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Normal Concentration of Uranium in Urine and Application of the Data to Its Biokinetics

Abstract: A method was developed to determine the concentration of uranium (238U) in urine. This method involved preconcentration of uranium from urine with calcium phosphate neutron activation followed by simple radiochemical separation. Using this method, it was possible to detect 0.2 ng of 238U. The average and geometric mean concentration of uranium found in urine of subjects from a normal background environment was 12.8 and 9.4 ng L-1, respectively. The concentration of uranium in the urine and the daily intake of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(22 citation statements)
references
References 0 publications
2
19
0
1
Order By: Relevance
“…A previous nonrandom subsample from NHANES III (n = 499) (Ting et al, 1999) and other small populations have shown urinary concentrations that are similar to those in NHANES 1999(Dang et al,1992Galletti, 2003;Karpas et al,1996;Tolmachev et al, 2006). Older studies have demonstrated urinary uranium concentrations that are consistent with levels in the U.S. population, in that the levels were below their respective detection limits (Byrne et al, 1991;Hamilton et al, 1994;Komaromy-Hiller et al, 2000).…”
Section: Biomonitoring Informationmentioning
confidence: 88%
“…A previous nonrandom subsample from NHANES III (n = 499) (Ting et al, 1999) and other small populations have shown urinary concentrations that are similar to those in NHANES 1999(Dang et al,1992Galletti, 2003;Karpas et al,1996;Tolmachev et al, 2006). Older studies have demonstrated urinary uranium concentrations that are consistent with levels in the U.S. population, in that the levels were below their respective detection limits (Byrne et al, 1991;Hamilton et al, 1994;Komaromy-Hiller et al, 2000).…”
Section: Biomonitoring Informationmentioning
confidence: 88%
“…High exposure was defined as urine total uranium concentrations greater than or equal to 0.10 lg/g creatinine, which is the exposure cutpoint utilized in previous years. While there is no generally accepted standard normal urine uranium value, we chose a value intermediate between, at the low end, several estimates of mean urine uranium concentration in non-exposed populations in the literature (0.011-0.022 lg/l) (Dang et al 1992;Medley et al 1994;Ting et al 1999) and, at the high end, upper dietary limits due to natural uranium in soil and ground water (up to 0.35 lg/l) urine (ICRP 1974).…”
Section: Urine Uranium As a Binary Variablementioning
confidence: 99%
“…Urinary excretion of uranium as a function of the measurement technique (non-exposed workers). Les valeurs obtenues sont en bon accord avec les donnĂ©es bibliographiques, bien que des variations significatives puissent ĂȘtre mises en Ă©vidence selon le pays, la rĂ©gion concernĂ©e et selon les mĂ©thodes de dosage mises en oeuvre (Dang, 1989 ;Dang, 1992;Harduin, 1994;Michaud, 1985 ;Shiraishi, 1992;Singh, 1990;Wrenn, 1985 ;Wrenn, 1992).…”
Section: Tableau IVunclassified